Common‐garden experiment reveals clinal trends of bud phenology in black spruce populations from a latitudinal gradient in the boreal forest. (25th January 2021) - Guo, Xiali; Klisz, Marcin; Puchałka, Radosław; Silvestro, Roberto; Faubert, Patrick; Belien, Evelyn; Huang, Jianguo; Rossi, Sergio
Abstract: Climate warming is modifying the movement of air masses over Northern latitudes, producing warming and cooling events across the boreal regions. These new conditions changes may mismatch plant phenology from weather conditions, and affect the growing period of trees. Understanding the processes of local adaptation in bud phenology can help to predict the response of plants to these rapid and unexpected environmental changes. Our study monitored bud burst and bud set weekly during four growing seasons in black spruce [ Picea mariana (Mill.) B.S.P.] saplings planted in a common garden and originating from five provenances representing the whole latitudinal distribution of the closed boreal forest in Quebec, Canada. We compared the variance in bud phenology among populations and years, and analysed the relationships with temperatures at the origin sites. Bud burst and bud set occurred in mid‐May and mid‐July, respectively, with a large variability among provenances and between the study years. A delayed bud phenology was observed in the provenances from warmer sites, with bud burst and bud set being 1.1 and 1.4 days later for every additional degree in mean annual temperature at the origin site respectively. Populations with earlier bud bursts also showed earlier bud sets, thus the growing season was similar among provenances. The heritability of bud set was higher than that of bud burst, with estimates of 0.26 and 0.21 respectively. On average, variance in bud phenology among provenances reached 5.3%, which was higher than that within provenances (2.6%). The factor year explained 37.7%–69.7% of the variance in bud phenology. Synthesis . The findings demonstrate the evolutionary response to climate variations in the boreal biome. Endogenous and environmental components have different effects on the phases of bud burst and bud set. This complex interaction among drivers of bud phenology may prevent reliable predictions of changes in the growing season under changing climate. An earlier growth reactivation due to higher spring temperatures could result in higher frost risks to the developing buds. Despite a longer period for photosynthesis expected for the evergreen black spruce under warmer conditions, the period spent for bud development could remain unchanged. Abstract : The findings demonstrate the evolutionary response to climate variations in the boreal biome. Endogenous and environmental components have different effects on the phases of bud burst and bud set. This complex interaction among drivers of bud phenology may prevent reliable predictions of changes in the growing season under changing climate. An earlier growth reactivation due to higher spring temperatures could result in higher frost risks to the developing buds. Despite a longer period for photosynthesis expected for the evergreen black spruce under warmer conditions, the period spent for bud development could remain unchanged.